Feasibility of transoral robotic selective neck dissection with or without a postauricular incision for papillary thyroid carcinoma: A pilot study - Tae, Kyung; Choi, Hae Won; Ji, Yong Bae; Song, Chang Myeon; Park, Jung Hwan; Kim, Dong Sun (Frontiers in Surgery, 2022)
Background The study aimed to evaluate the feasibility of transoral robotic selective neck dissection (SND) with or without a postauricular incision for papillary thyroid carcinoma (PTC). Methods We studied 14 patients with PTC who underwent robotic SND via the transoral or combined transoral and postauricular approaches. Results The transoral approach was performed on 10 patients for dissection of levels III and IV. An additional postauricular incision was made on 4 patients for dissection of level II in addition to levels III, IV, and V. The operation was completed successfully in 13 patients, except 1 patient with the procedure conversion due to uncontrolled bleeding from the internal jugular vein. The mean numbers of removed lymph nodes in the lateral compartment were 23.1 ± 9.4 and 38.3 ± 8.5 in the transoral and combined groups. Transient recurrent laryngeal nerve palsy occurred in 1 patient, transient hypoparathyroidism in 3 patients, and chyle leakage in 1 patient. There were no hematomas, mental nerve injuries, surgical space infections, or CO2 embolisms. Conclusion Transoral robotic SND is feasible with or without a postauricular incision.